2019
DOI: 10.1186/s12883-019-1492-2
|View full text |Cite
|
Sign up to set email alerts
|

Persistent trigeminal artery in a patient with posterior circulation stroke treated with rt-PA: case report

Abstract: BackgroundA persistent trigeminal artery (PTA) is a non-involuted embryonic vessel that connects the cavernous part of the internal carotid artery with the posterior circulation. In the adult it is associated with multiple pathological conditions including trigeminal neuralgia, ophthalmoplegia, hypopituitarism, intracavernous fistula, brain aneurysms and posterior circulation strokes. The latter may occur through steal phenomena or thrombosis in the anterior circulation. PTA associated vertebrobasilar hypoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…According to Da-Ping et al (5), it is unclear whether PTA is associated with ischemic cerebrovascular disease. However, Ferreira et al (3) reported that patients with PTA and basilar hypoplasia had hypoperfusion in the posterior fossa, and therefore were more susceptible to ischemic events. Engelhardt et al ( 4) stated that as the number of collaterals increased, infarction became smaller.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Da-Ping et al (5), it is unclear whether PTA is associated with ischemic cerebrovascular disease. However, Ferreira et al (3) reported that patients with PTA and basilar hypoplasia had hypoperfusion in the posterior fossa, and therefore were more susceptible to ischemic events. Engelhardt et al ( 4) stated that as the number of collaterals increased, infarction became smaller.…”
Section: Discussionmentioning
confidence: 99%
“…PTA accounts for approximately 85% of all persistent presegmental arteries (2). In digital subtraction angiography (DSA), PTA is observed at a rate ranging from 1 in a 1,000 to 6 in 1,000, and it is usually unilateral (2,3). In radiological examinations, almost all cases are detected incidentally.…”
Section: Introductionmentioning
confidence: 99%
“…The PTA has been identified as a rare cause of cranial nerves dysfunction, including incomplete oculomotor and abducens nerve palsies, trigeminal neuralgia and hemifacial spasm. The ischemic events related to the PTA are rare and can occur through the steal phenomenon or thrombosis in anterior circulation [16,21]. Typically, persistent trigeminal artery aneurysms (PTAA) are discovered incidentally in patients with subarachnoid hemorrhage (SAH) due to the rupture of a simultaneous aneurysm in another localization.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the presence of PTA may also be associated with ischemic stroke [18][19][20]. In patients with PTA and vertebrobasilar hypoplasia, the vascular supply to the posterior fossa may tend to decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Arra'ez-Aybar et al reported that most of the PTAs originated from the posterior wall of the cavernous segment of the ICA (C4) and a small number of PTAs originated from the petrous segment [9]. The C4 segment is often reported as the origin of PTAs [9,[17][18][19][20][21]. Most of the PTA cases in the present study (85%) originated from the posterior wall of the cavernous segment (C4) of the ICA, and few (15%) originated from the petrous part.…”
Section: Discussionmentioning
confidence: 99%